Correlation of Brain Derived Neurotrophic Factors (BDNF) With Maternal and Perinatal Outcome in Preeclampsia - Mayuliani, Mayuliani; Yusrawati, Yusrawati; Defrin, Defrin (Andalas Obstetrics And Gynecology Journal, 2021)
Objective: To analyze the correlation between BDNF and maternal and perinatal outcomes in preeclampsia.Methods: This was an observational analytic study with a cross-sectional design on 73 pregnant women with preeclampsia. The study began in January 2020 to June 2020 in the Obstetrics and Gynecology Department of Dr M. Djamil Hospital Padang.Results: The mean BDNF levels of pregnant women with preeclampsia were 519.9Â Â± 325.4 pg/ml. The correlation between BDNF and systolic blood pressure, diastolic blood pressure, and Mean Arterial Pressure was negatively correlated (r = -0.145, -0.1, and -0.218), with a weak correlation. There was no statistically significant relationship between BDNF and systolic blood pressure, diastolic blood pressure, and mean arterial pressure (p> 0.05). BDNF correlation with infant birth weight and the birth length was positively correlated (0.196 and 0.205) with a weak correlation. The correlation between BDNF level and Apgar score was negatively correlated (-0.039 and -0.054) with a weak correlation. There was no statistically significant correlation between BDNF with birth weight, birth length, and Apgar score (p> 0.05).Conclusion: The mean BDNF level in preeclampsia was lower than normal pregnancy, there was a negative correlation between BDNF levels and maternal outcomes in preeclampsia with a weak correlation. There was a positive correlation between BDNF levels and perinatal outcomes (birth weight and birth length) in preeclampsia and there was a negative correlation between BDNF levels and Apgar score in preeclampsia with a weak correlation.Keywords: Brain Derived Neurotrophic Factors, Preeclampsia, Maternal Outcome, Perinatal Outcome